(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
An incomplete coelacanthiform specimen is described from the Dont Formation (Anisian, Middle Triassic) of Kühwiesenkopf/Monte Prà della Vacca in the Northern Dolomites (NE Italy). Even if the incompleteness of the specimen does not allow a reliable taxonomic assignment at generic level, it increases our understanding of Middle Triassic coelacanthiform diversity in the western Tethys.